One-Step Electrodeposition of Nanosized Cobalt Oxy/Hydroxide Composites Obtained from Deep Eutectic Solvent as Multifunctional Catalysts - Sakita, Alan M. P. [UNESP]; Della Noce, Rodrigo; Benedetti, Assis [UNESP]; Garcia-Amoros, Jaume; Valles, Elisa (Electrochemical Soc Inc, 2018)
Glyceline deep eutectic solvent, with a controlled amount of water, has been demonstrated as a useful medium for the electrochemical production of oxidized species of cobalt enabling, in turn, the use of this kind of solutions to electrodeposit species different than metals and alloys. The oxidized species have been fabricated directly over glassy carbon and nickel substrates in a single step with the concomitant formation of a poly-glycerol porous structure integrating the metallic oxides. Remarkably, the resulting composite (polymer + oxides) can be exploited as a multifunctional heterogeneous catalyst. On one hand, our composite material is an excellent and readily preparable electrode for the non-enzymatic amperometric detection and quantification of glucose. On the other hand, the composites reported herein are also efficient catalysts for the oxygen evolution reaction (OER) in alkaline solutions, displaying their maximum activity after the dissolution of the polymer and subsequent liberation of the oxidized cobalt species. (C) 2018 The Electrochemical Society.